Simulation workshops with first year midwifery students - Catling, C.; Hogan, R.; Fox, D.; Cummins, A.; Kelly, Michelle; Sheehan, A. (Churchill Livingstone, 2016)
Simulated teaching methods enable a safe learning environment that are structured, constructive and reflective. We prepared a 2-day simulation project to help prepare students for their first clinical practice. A quasi-experimental pre-test – post-test design was conducted. Qualitative data from the open-ended survey questions were analysed using content analysis. Confidence intervals and p-values were calculated to demonstrate the changes in participants' levels of understanding/ability or confidence in clinical midwifery skills included in the simulation. 71 midwifery students participated. Students rated their understanding, confidence, and abilities as higher after the simulation workshop, and higher still after their clinical experience. There were five main themes arising from the qualitative data: having a learning experience, building confidence, identifying learning needs, developing communication skills and putting skills into practise. First year midwifery students felt well prepared for the clinical workplace following the simulation workshops. Self-rated understanding, confidence and abilities in clinical midwifery skills were significantly higher following consolidation during clinical placement. Longitudinal studies on the relationship between simulation activities and student's overall clinical experience, their intentions to remain in midwifery, and facility feedback, would be desirable.